Proteomics and metabolomics analyses reveal the cucurbit sieve tube system as a complex metabolic space. (7th July 2016) - Hu, Chaoyang; Ham, Byung‐Kook; El‐shabrawi, Hattem M.; Alexander, Danny; Zhang, Dabing; Ryals, John; Lucas, William J.
Summary: The plant vascular system, and specifically the phloem, plays a pivotal role in allocation of fixed carbon to developing sink organs. Although the processes involved in loading and unloading of sugars and amino acids are well characterized, little information is available regarding the nature of other metabolites in the sieve tube system (STS) at specific sites along the pathway. Here, we elucidate spatial features of metabolite composition mapped with phloem enzymes along the cucurbit STS. Phloem sap (PS) was collected from the loading (source), unloading (apical sink region) and shoot–root junction regions of cucumber, watermelon and pumpkin. Our PS analyses revealed significant differences in the metabolic and proteomic profiles both along the source–sink pathway and between the STSs of these three cucurbits. In addition, metabolite profiles established for PS and vascular tissue indicated the presence of distinct compositions, consistent with the operation of the STS as a unique symplasmic domain. In this regard, at various locations along the STS we could map metabolites and their related enzymes to specific metabolic pathways. These findings are discussed with regard to the function of the STS as a unique and highly complex metabolic space within the plant vascular system. Significance Statement: In angiosperms, it is well known that the phloem sieve tube system loads and delivers sugars, amino acids and signaling molecules to developing sinks and/or storage organs, but little is known about other metabolites that use this system. Here we show that the phloem sieve tube system also accumulates a broad range of metabolites, and that the enzymes and substrates for such metabolites are site specific.